Cognitive Effect Following a Blended (Face to Face and Videoconference-Delivered) Format Mindfulness Training - Wang, Grace Y.; Taylor, Tamasin; Sumich, Alexander; Krägeloh, Chris; Lee, Carol Qinglian; Siegert, Richard J. (Frontiers in Psychology, 2021)
While evidence supports the feasibility of online mindfulness training (MT), the effect of this approach on cognition remains unclear. The present study investigated changes in cognition following a newly developed 6-week videoconference-delivered MT programme on cognitive function in two groups. The first group (n=17) had two baseline assessments prior to MT (3 weeks after Group two (n=15)) to allow for evaluation of practice and learning effects. Four participants from each group were excluded from the final analysis due to missing data. Following MT, there was an improvement in switching of attention, working memory, executive function, and social cognition, but some of these effects were not easily accounted for by learning or practice effects. No significant changes were found on tasks measuring sustained attention, cognitive flexibility and inhibition, information processing, and sensory-motor function. Our findings suggest that domain-specific cognition might be enhanced by a brief videoconference-delivered MT, and larger, controlled studies to delineate the effects of online MT on subdomains of cognition are needed.